Credit Risk and Liquidity Risk with Firm Size as Moderator Variable on Profitability in State-Owned Banking - Dewi, Gusti Ayu Putri Pradnya; Pradnyani, Ni Luh Sri Purnama; Suryantari, Eka Putri (Journal of Applied Sciences in Accounting, Finance, and Tax, 2026)
This study aims to examine the effect of credit risk and liquidity risk on profitability, with firm size as a moderating variable, in state-owned banks listed on the Indonesia Stock Exchange during the 2015–2024 period. The objective of this study is explicitly to analyze both the direct effects of financial risks and the moderating role of firm size in influencing bank profitability, providing a more comprehensive understanding of banking performance. The study provides a comprehensive understanding of how firm-specific characteristics influence the relationship between financial risks and profitability. Grounded in Agency Theory, this study emphasizes that information asymmetry between principals and agents can lead to inefficient risk-taking decisions, where credit risk (proxied by Non-Performing Loans/NPL) and liquidity risk (proxied by Loan to Deposit Ratio/LDR) directly affect profitability (measured by Return on Assets/ROA) through increased costs and reduced financial efficiency. Firm size, measured as the natural logarithm of total assets, is expected to moderate these relationships because larger banks generally possess stronger asset structures, better governance mechanisms, and greater risk absorption capacity. A quantitative approach was employed using secondary data from the annual reports of four state-owned banks over a ten-year period, specifically covering the 2015–2024 observation years, resulting in 40 observations, and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS version 4.1.1.6. The findings indicate that credit risk and liquidity risk have a significant negative effect on profitability, while firm size significantly weakens this negative impact, demonstrating a quasi-moderating role. This indicates that firm size acts as a buffering variable that reduces the intensity of risk effects rather than eliminating them entirely, highlighting its strategic importance in banking stability. The study contributes both theoretically and practically by strengthening the application of Agency Theory in explaining risk–profitability relationships and by providing empirical evidence on the moderating role of firm size in state-owned banks in Indonesia, which remains relatively underexplored in prior research.